Eksplorasi Gerak Untuk Meningkatkan Percaya Diri Anak Korban Kekerasa Keluarga - Apriliani Rafika Dewi (Jurnal Pendidikan Tari, 2021)
The purpose of this study was to obtain data on the confidence of children victims of family violence. The study uses an action research model by Kemmis and MC Taggart with the application of motion exploration. The study used two cycles, which included planning, action, observation, and reflection. The results showed that the exploration of motion can increase the confidence of children victims of family violence. Based on the results of the pre-cycle 52.4%, cycle I increased to 74%, and cycle II to 83.6%. The conclusion of the study is that the application of exploration of motion can increase the confidence of children victims of family violence. The benefit of this study is that the exploration of motion can be used as dance therapy to increase confidence.